Mechanics for engineers dynamics - Hibbeler, R.C (Pearson Education South Asia, 2012)
The first book published in the Beer and Johnston Series, Mechanics for Engineers: Dynamics is a scalar-based introductory dynamics text providing first-rate treatment of rigid bodies without vector mechanics. This new edition provides an extensive selection of new problems and end-of-chapter summaries. This text is ideal for civil and mechanical engineering professionals. ¿ MasteringEngineering, the most technologically advanced online tutorial and homework system available, can be packaged with this edition.